2002
DOI: 10.1111/j.1471-0528.2002.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twin‐to‐twin delivery interval on umbilical cord blood gas in the second twins

Abstract: Objective To examine the effect of twin-to-twin delivery interval on the umbilical cord blood gas status of the second twin following vaginal delivery. Design A retrospective study.Setting The department of obstetrics and gynaecology in a university teaching hospital.Population Twin deliveries at or beyond 34 weeks of gestation over a period of five years, with the first twin delivered vaginally. Twins with any antepartum complications including discordant growth, intrauterine growth restriction, intrauterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
2
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 9 publications
10
51
2
12
Order By: Relevance
“…These observations have been supported by another cohort study that found a higher risk of metabolic acidosis of the second twin after a TTDT of more than 60 minutes (Edris et al, 2006). These data are in line with those of a study of 118 patients showing a significant correlation between all umbilical cord blood gas parameters of the second twin and TTDT (Leung et al, 2002). Like us, Leung also focused on those twin pairs at or beyond 34 weeks of gestation and vaginal delivery of twin I.…”
Section: Discussionsupporting
confidence: 77%
“…These observations have been supported by another cohort study that found a higher risk of metabolic acidosis of the second twin after a TTDT of more than 60 minutes (Edris et al, 2006). These data are in line with those of a study of 118 patients showing a significant correlation between all umbilical cord blood gas parameters of the second twin and TTDT (Leung et al, 2002). Like us, Leung also focused on those twin pairs at or beyond 34 weeks of gestation and vaginal delivery of twin I.…”
Section: Discussionsupporting
confidence: 77%
“…Respecto a estudios previamente publicados con un objeto similar de estudio, algunos autores concluyen que el pH del segundo gemelo es más bajo que el del primero (1,3,7,11-16) y parece deteriorarse con más rapidez (17), también describen una correlación negativa entre el intervalo de nacimiento entre gemelos y las diferencias en el pH de ambos gemelos o el valor del pH de cordón del segundo (11,(17)(18)(19)(20). Sin embargo, no tienen en consideración el estado ácido-base del primer gemelo, ni el deterioro del pH de cordón umbilical del segundo gemelo respecto al primero.…”
Section: Discussionunclassified
“…Il n'existe pas de données scientifiques en faveur d'un tel examen. Quatre-vingt-dix-huit pour cent des répondants conseillent une analgésie péridurale qui faciliterait les gestes obstétricaux et permettrait de réduire le risque d'avoir une césarienne en cours de travail selon Williams et al [32] [33]. On sait aussi que J2 à terme serait à plus haut risque que J1 de mourir au cours du travail (n = 2436 jumeaux à terme), en particulier par anoxie per-partum (p = 0,02) [34].…”
Section: Discussionunclassified